Comparative Study of The Physiological Condition of Six Tree Species to Air Pollution in Depok City, West Java - Ayunda, Ajenk; Yuniati, Ratna; Handayani, Windri (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: Air pollution is a threat to the environment. Sources of air pollutants in urban environments can be in the form of dust, heavy metals, and hydrocarbons. Plants can help clean air pollutants from the atmosphere by absorption through the stomata, accumulating them, or by adsorption on the leaf surface. The Air Pollution Tolerance Index (APTI) is used as an evaluation benchmark for the Physiological conditions of plants exposed to air pollution. This research aims to study the physiological conditions of six tree species in air conditions in the Depok City area and to assess the plants' tolerance level based on the APTI calculation. Methods: The physiological parameters measured to calculate APTI were ascorbic acid, total chlorophyll, leaf extract pH, and Relative Water Content (RWC). The six tree species used as objects in this study were Artocarpus altilis, Artocarpus heterophyllus, Bauhinia purpurea, Ficus septica, Filicium decipiens, and Nephelium lappaceum. Results: Differences in the physiological conditions of six tree species in the Depok City area based on the average ascorbic acid values, total chlorophyll, leaf extract pH, and RWC. In addition, there are also differences in APTI parameters between the two research locations. Conclusions: Filicium decipiens is the plant species with the highest APTI, while Artocarpus heterophyllus has the lowest. Based on the APTI scores, Bauhinia purpurea, Ficus septica, Filicium decipiens, Nephelium lappaceum belong to moderately tolerant category, Artocarpus altilis belongs to an intermediate category, Artocarpus heterophyllus belongs to sensitive category.